Archaeology and history of Toraijin : human, technological, and cultural flow from the Korean Peninsula to the Japanese Archipelago c. 800 BC-AD 600 - Rhee, Song Nai, 1935- (Archaeopress Archaeology, 2021)
In light of the recently uncovered archaeological data and ancient historical records, this book offers an overview of the 14 centuries-long Toraijin story, from c. 800-600 BC to AD 600, exploring the fundamental role these immigrants, mainly from the Korean Peninsula, played in the history of the Japanese archipelago during this formative period.